Product management system for Syaheer Rezali Cosmetic / Nur Athirah Mohd Kamaruzzaman - Mohd Kamaruzzaman, Nur Athirah (2017)
Product is a substance that is manufactured for sale. There are many types of product but this project focus on the management of product in a cosmetic shop. Syaheer Rezali Cosmetic shop focus on cosmetic and beauty product. Currently staff record the information in a log book that can cause information loss due to misplaced of the log book. There is also a problem of duplication of data recorded in the log book. This project will be focusing on the development of the product management system for the Syaheer Rezali Cosmetic shop. The purpose in developing this system was to collect, record and manage the product that is available in the stakeholder shop. The product management system can help the user to record and manage the product in the shop. To do all the process and development of the project, a waterfall methodology has been chosen consist of three phase, which is requirement gathering and analysis phase, system design phase and system development phase. Based on the methodology phase that have been chosen, the Software Requirement Specification and Software Design Documentation is delivered. Using the Software Requirement Specification and Software Design Documentation the system is developed. The system develop can improve the product management in the stakeholder shop and smooth the management process. The development of product management system show that the system is useful for the management of product in the stakeholder shop. Even though the project has been complete, there are a lot of enhancement need to be done in order to remove the limitations. The system has some limitation in term of usability which is the system cannot record the time of user login into the system and the system do not provide several important functions such as a function to calculate payment and to keep track the supplier of the product. Due to this limitation, the recommendation for future work for the system is by adding new feature and function to keep track the user login time and to calculate the payment made by the customer.